Regulatory Responses to Platform Dominance: Insights from Global Digital Markets - Vebritha, Silvy (Legalis : Journal of Law Review, 2025)
This study reviews global regulatory responses to platform dominance in digital markets. It examines the interplay between competition law and data protection, focusing on ex-ante approaches such as the EU Digital Markets Act. Using a narrative review of peer-reviewed literature, the findings show that preventive frameworks are more effective than traditional ex-post models in curbing anti-competitive practices. Evidence highlights systemic risks from data asymmetry and algorithmic manipulation, particularly in developing countries with limited enforcement capacity. The review underscores the need for coherent policies that balance innovation, fairness, and user rights, recommending further research on algorithmic accountability, harmonized governance, and the socioeconomic impacts of digital regulation.